2023
DOI: 10.1002/mp.16771
|View full text |Cite
|
Sign up to set email alerts
|

The LET trilemma: Conflicts between robust target coverage, uniform dose, and dose‐averaged LET in carbon therapy

Albin Fredriksson,
Lars Glimelius,
Rasmus Bokrantz

Abstract: BackgroundLinear energy transfer (LET) is closely related to the biological effect of ionizing radiation. Increasing the dose‐averaged LET (LETd) within the target volume has been proposed as a means to improve clinical outcome for hypoxic tumors. However, doing so can lead to reduced robustness to range uncertainty.PurposeTo quantify the relationship between robust target coverage, target dose uniformity, and LETd, we employ robust optimization using dose‐based and LETd‐based functions and allow varying amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This effect is mitigated by creating less steep distal edges, but this also decreases the LET d . Hence, the antagonism between high LET d , uniform dose, and robustness has recently been dubbed the LET d trilemma [52]. In spite of this, we found that even the LET-optimized plans with "watered down" LET d (~3-3.5 keV/µm) to achieve better robustness still outperform SFO plans in terms of TODRs and minimum average RBE-dose coverage.…”
Section: Treatment Planning Considerations For Let D Optimizationmentioning
confidence: 73%
See 1 more Smart Citation
“…This effect is mitigated by creating less steep distal edges, but this also decreases the LET d . Hence, the antagonism between high LET d , uniform dose, and robustness has recently been dubbed the LET d trilemma [52]. In spite of this, we found that even the LET-optimized plans with "watered down" LET d (~3-3.5 keV/µm) to achieve better robustness still outperform SFO plans in terms of TODRs and minimum average RBE-dose coverage.…”
Section: Treatment Planning Considerations For Let D Optimizationmentioning
confidence: 73%
“…To investigate the effects of density uncertainty on LET d optimization, we performed robust evaluations for an example patient; a more detailed analysis on robustness and LET d optimization for carbon ion beams is presented by Fredriksson et al [52]. Fredriksson et al describe an LET d trilemma in which improving two of the factors of range robustness, uniform dose, and high LET d comes at the expense of the third factor.…”
Section: Robust Evaluationmentioning
confidence: 99%
“…24 The implementation specifications of LET d optimization is described in another work. 22 In order to increase the LET d in the CTV-HD, the "minimum LET d " optimization function (L min ) of the TPS was utilized for the seven PTV-HD fractions. The nine PTV-LD fractions were not re-optimized and their reference plans were used.…”
Section: Let D Optimization and Treatment Plan Evaluationmentioning
confidence: 99%
“…Target: Increasing the LET d in the tumor and maintaining the robustness is not possible without accepting certain deterioration in the RBE-weighted dose uniformity. 22 The clinical goals related to target coverage were therefore slightly adapted,allowing 10% over-and underdosage in the CTV-HD and 5% under-dosage in the GTV as summarized in Table 2. To have a more thorough investigation on the different optimization parameters, additional low-prio-target-LEM-goals were determined as summarized in Table S2.…”
Section: Evaluation Of Rbe-weighted Dose (Lem)mentioning
confidence: 99%
See 1 more Smart Citation